Neural Network as a Tool for Detection of Wine Grapes - Doležel, Petr; Škrabánek, Pavel; Gago, Lumír (Springer International Publishing AG, 2016)
The recognition of wine grapes in real-life images is a serious issue solved by researches dealing with precision viticulture. The detection of wine grapes of red varieties is a well mastered problem. On the other hand, the detection of white varieties is still a challenging task. In this contribution, detectors designed for recognition of white wine grapes in real-life images are introduced and evaluated. Two representations of object images are considered in this paper; namely, vector of normalized pixel intensities and histograms of oriented gradients. In both cases, classifiers are realized using feedforward multilayer neural networks. The detector based on the histograms of oriented gradients has proven to be very effective by cross-validation. The results obtained by its evaluation on independent testing data are slightly worse; however, still very good. On the other hand, the representation using the vector of normalized pixel intensities was stated as insufficient.
Neuronová síť jako pomůcka pro detekci bobulí vinné révy
Keywords: Grape detection; Neural networks; Image processing; Precision viticulture; HOG features; Detekce bobulí; umělé neuronové sítě; zpracování obrazu; přesné vinohradnictví; HOG vlastnosti